2017
DOI: 10.3390/ma10101125
|View full text |Cite
|
Sign up to set email alerts
|

Design and Additive Manufacturing of 3D Phononic Band Gap Structures Based on Gradient Based Optimization

Abstract: We present a novel approach for gradient based maximization of phononic band gaps. The approach is a geometry projection method combining parametric shape optimization with density based topology optimization. By this approach, we obtain, in a two dimension setting, cellular structures exhibiting relative and normalized band gaps of more than 8 and 1.6, respectively. The controlling parameter is the minimal strut size, which also corresponds with the obtained stiffness of the structure. The resulting design pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 46 publications
0
32
0
2
Order By: Relevance
“…These systems have a particular dispersion relation with the presence of band gaps [3]. Recently, with the advent of 3D printing, more complex and efficient designs are allowed [4][5][6][7]. In the particular case of rigid scatterers embedded in a fluid host, the system is known as sonic crystal because they are particularly suited for sound waves [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These systems have a particular dispersion relation with the presence of band gaps [3]. Recently, with the advent of 3D printing, more complex and efficient designs are allowed [4][5][6][7]. In the particular case of rigid scatterers embedded in a fluid host, the system is known as sonic crystal because they are particularly suited for sound waves [8].…”
Section: Introductionmentioning
confidence: 99%
“…s . ∆ slit = ∆l 1 + ∆l 2 is the length correction, where ∆l 1 is the length correction given by the pressure radiation at the discontinuity from the neck duct to the cavity of the Helmholtz resonator, and ∆l 2 comes from the radiation at the discontinuity from the neck to the principal waveguide (see reference [38]) given by Equation (4) and Equation (5). It is important to note that, due to the symmetry of each resonator, the radiation correction of the slit to the free space must be applied at both sides of the structure.…”
mentioning
confidence: 99%
“…There are two formation mechanisms of the elastic band gap in PCs: one is the Bragg scattering mechanism [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], and the other is the locally resonant mechanism. The wave length corresponding to the elastic band gap formed by Bragg scattering is generally equal to the lattice size or lattice constant, which restricts its application in engineering practice.…”
Section: Introductionmentioning
confidence: 99%
“…Further developments include substantial material research to optimize different metallic powders and minimize the grain size to improve resolution and surface roughness [28]. SLS and SLM have recently been successfully employed to build 3D phononic crystals for lower frequency operation [16,19].…”
Section: Choice Of Fabrication Technologymentioning
confidence: 99%
“…Numerical analysis usually focuses on the formation of a complete band gap between all types of propagation modes in an infinite lattice, or on a specific type of wave propagation through a semi-infinite lattice. Experimental acoustic transmission analysis is then often limited to only one primary propagation direction [16][17][18][19]. As early phononic crystal research has already shown, the band structure and transmission behavior will yield drastically different results for the complete, omnidirectional band gap and more application oriented directional band gaps for specific acoustic modes.…”
Section: Introductionmentioning
confidence: 99%